MUTU ORGANOLEPTIK & ANALISIS NILAI GIZI DONAT NUGGET IKAN PUYU (Anabas Testudineus) SUBSTITUSI PENAMBAHAN WORTEL (Daucus Carota L), JAGUNG (Zea Mays L) SEBAGAI ALTERNATIF MAKANAN TAMBAHAN BALITA STUNTING - Nurhamidah, Nurhamidah; Yensasnidar, Yensasnidar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Stunting is a chronic condition that describes stunted growth due to long-term malnutrition. Food is one of the basic needs of humans. One form of food that is often found among children and adults is nuggets. Puyu fish contains high levels of zinc, niacin, copper, calcium, water and protein. Carrot and corn have high vitamin and fibre content. The purpose of this study was to determine the organoleptic quality and nutritional value of donut nuggets of puyu fish (anabas testudineus) with the substitution of carrot (daucus carota L) corn (zea mays L) as an alternative additional food for stunted toddlers. This type of research is experimental using the complete randomised design (CRD) method consisting of control and 3 treatments with 2 repetitions. Organoleptic test, protein content test using kjeldahl method, fat content test using soxhlet method, carbohydrate content test using spectrophotometric method, calcium and zinc content test using X-Ray Fluorescence method, and fibre content test using gravimetric method.Based on the results of research on puyu fish nuggets with the substitution of carrot and corn additions, the resulting organoleptic test value of puyu fish nugget donuts, the highest average value of nugget colour is treatment P2 (4.10) with (the addition of 50 g carrots and 30 g corn), the highest average value of nugget aroma is treatment P2 (3.86) with (the addition of 50 g carrots and 30 g corn), the highest average value of nugget texture is treatment P2 (3. 92) with (addition of carrot 50 g and corn 30 g), the average value of the highest nugget taste is treatment P2 (3.92) with (addition of carrot 50 g and corn 30 g) and the best product with taste (colour, aroma, texture, and taste) is treatment P2 with (addition of carrot 50 g and corn 30 g) with an average of colour 3.78, aroma 3.86, texture 3.92, and taste 3.92. And from the nutritional value analysis of the best treatment, P2, contains 11.4977% protein content, 6.9997% fat content, 43.9423% carbohydrate content, 13.9000% calcium content, 0.4220% zinc content, and 98.0147% fibre content. This research is the utilisation of local food in the community as an alternative supplementary food for children under five who are stunted.Key Words : Puyu fish (anabas testudineus), Carrots, Corn, Toddler, Stunted growth.